Revealing the Best Strategy: A Comparative Study of PBL and PjBL in Enhancing Critical Thinking in Pancasila Education - Delfiyan Widiyanto; Hari Wahyono; Annisa Istiqomah; Sulthan Syifana; Khoirunnisa Ayu (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2025)
The purpose of this study is to compare the project-based learning and problem-based learning models in improving students' critical thinking skills in the Pancasila Education subject. This study used a quasi-experimental method with a quantitative approach. The research design used was a one-group pretest-posttest design. Through this design, both groups, namely the experimental class and the experimental class, were given an initial test (pre-test) to determine students' initial abilities before treatment, then given different treatments. The experimental class received learning with the Project Based Learning (PjBL) model, while the second experimental class used the Problem Based Learning (PBL) model. The results showed that Problem Based Learning was more effective in improving students' critical thinking skills compared to Project Based Learning. The PBL approach, which emphasizes the process of identifying, analyzing, and solving real problems, can encourage students to think critically and relate concepts to everyday life contexts. Meanwhile, in PjBL, although providing a project-based learning experience.Keywords: Project Based Learning, Problem Based Learning, Critical Thinking